Effect of Diet Enriched With Hemp Seeds on Goat Milk Fatty Acids, Transcriptome, and miRNAs - Cremonesi, Paola; Capra, Emanuele; Turri, Federica; Lazzari, Barbara; Chessa, Stefania; Battelli, Giovanna; Colombini, Stefania; Rapetti, Luca; Castiglioni, Bianca (Frontiers in Animal Science, 2022)
Nutritional strategies, such as supplementation with feed rich in unsaturated fatty acids, can increase the healthy property of milk in dairy ruminants, even if their effect throughout the pathways/genes involved in these processes are not properly defined. The next-generation sequencing technology allows the whole transcriptome characterization under given conditions, thereby providing deeper knowledge of the cell’s activity in such conditions. In addition to this, microRNAs have recently been described to be potent post-transcriptional regulators in fatty acid metabolism by targeting lipid metabolism genes. In this study, RNA-sequencing was used to investigate the goat milk transcriptome and miRNAs following supplemental feeding enriched with hemp seeds in order to point out the general biological mechanisms underlying the effects related to milk fat metabolism. Ten pluriparous Alpine goats fed with the same pre-treatment diet for 40 days were, then, arranged to two dietary treatments consisting of control (C) and hemp seeds (H) supplemented diet. Milk samples were collected at 40 (Time point = T0) and 140 days of lactation (Time point = T1). Milk fatty acid (FA) profiles revealed a significant effect of hemp seeds that determined a strong increment in the preformed FA, causing a reduction in concentration of de novo FA. Monounsaturated and polyunsaturated n-3 FA were increased by hemp treatment, determining a reduction in n-6/n-3 ratio. RNA was extracted from the pelleted milk cells and transcriptomic analysis was conducted by Illumina RNA sequencing. A total of 3.835 genes were highly differentially expressed (p-value < 0.05, Fold Change > 1.5 and FDR < 0.05) in H group. Functional analyses evidenced changes in metabolism, immune, and inflammatory responses. Furthermore, modifications in feeding strategies affected also key transcription factors regulating the expression of several genes involved in milk fat metabolism, as PPARs (Peroxisome Proliferative Activated Receptor). Moreover, thirty-eight (15 known and 23 novel) differentially expressed miRNAs were uncovered in the H group and their potential functions were also predicted. This study provides noteworthy insights into the molecular changes occurring as a result of hemp seed supplementation in goat diet and broadens our understanding of the relationship between nutrients variation and phenotypic effects.